A Study of Nonlinear Fractional q-Difference Equations with Nonlocal Integral Boundary Conditions - Ahmed Alsaedi; Bashir Ahmad; Hana Al-Hutami (Abstract and Applied Analysis)
This paper is concerned with the existence and uniqueness of solutions for a boundary value problem of nonlinear fractional q-difference equations with nonlocal integral boundary conditions. The existence results are obtained by applying some well-known fixed point theorems and illustrated with examples.